توجيه ظواهر الرسم عند الإمام ابن الجزري في كتابه النشر-دراسة تحيلية - شلالبة, نسيبة; منصور, حليمة (University of Eloued-جامعة الوادي, 2022)
"تناولنا في هذه المذكرة توجيه ظواهر الرسم العثماني، وكان الإمام ابن الجزري وكتابه النشر موضوع دراستنا. قمنا أولاً بتعريف الإمام؛ وأخذنا صورة عامّة على حياته الشخصيّة والعلميّة التي كانت لها الدور الكبير فيما وصل إليه شيخ القرّاء ابن الجزري، ثمّ عرفنا بكتابه ""النشر في القراءات العشر""وذلك من خلال ذكر موضوعاته ومنهجه في القراءات والرسم العثماني. ثم تطرقنا لتعريف الرسم العثماني وظواهره، وموقف العلماء منها؛ حيث بيّنت لنا هاته الدراسة فوائد الرسم العثماني ومدى اهتمام الإمام ابن الجزري بهذه الظواهر تعليلاً وتفسيراً؛ حيث توصلنا إلى أهم الاعتبارات التي كان يعتمدها في توجيهاته."In this thesis, we addressed the orientation of the Ottoman painting phenomena where Imam Ibn al-Jazari and his publishing book were the subjects of our study. We first gave a glance at the imam's personal and scientific life, which had a significant role in reaching the Ibn Al Jazri this status, then we identified his book "Publishing in the Ten Readings" by mentioning his subjects, approach and drawing in the Ottoman readings. Finally, we headed towards the definition of the ottoman painting, its phenomena and the scientist's point of view on it.This study educed the benefits of Ottoman painting and the extent of Imam Ibn al-Jazari's interest in it and its manifestations in explanation and interpretation;We concluded with the most important considerations he has adopted in his guidance
مذكرة ماستر
Keywords: "الرسم العثماني ابن الجزري النشر توجيه ظواهر الرسم "; ottoman painting Ibn Al-Jazari publishing Directing graphic phenomena